A new method for detecting nucleolus organizer regions in fish chromosomes using denaturation and propidium iodide staining - Rab, P; Reed, K M; Ponce de León, F A; Phillips, R B (Biotechnic & histochemistry, 1996)
A rapid method for detecting nucleolus organizer regions (NORs) in fish chromosomes based on thermal denaturation and staining with propidium iodide is described. Under epifluorescence, the NORs of 15 fish species from six families could be detected. This protocol differentiates constitutive heterochromatin in mammalian and avian chromosomes, and in some cases, heterochromatic blocks in fish chromosomes. The staining of NORs of fish chromosomes with propidium iodide following denaturation with formalin is likely the result of differential denaturation of the rDNA due to the thermal characteristics of AT- and GC-rich domains of the rDNA cistron. This technique provides a new useful marker for descriptive fish cytogenetic studies.
Keywords: Animals; Staining and Labeling; propidium; organizátor jadérka; Propidium; Coloring Agents; zvířata; Chromosomes; Fishes; chromozomy; Nucleolus Organizer Region; barvicí látky; barvení a značení; ryby